2013
DOI: 10.2174/138955713804999775
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Activity of Coumarins and Flavonoids

Abstract: Coumarins and flavonoids are heterocyclic molecules that have been associated with beneficial effects on human health, such as reducing the risk of cancer, diabetes, cardiovascular and brain diseases. These effects are thought to be related to the radical scavenging effect, due to their antioxidant activities, along with other possible mechanisms, such as anti-inflammatory properties and interaction with several enzymes. Over the past two decades, there have been an increasing number of publications on coumari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 144 publications
3
60
0
1
Order By: Relevance
“…However, CHCl 3 , SLG, and n -hexane extracts significantly reduced the lipid peroxidation. The phytochemical screening revealed the presence of low polarity compounds, such as coumarins and alkaloids, both inhibitors of lipid peroxidation [53, 54]. These results are in accordance with previous studies on antioxidant activity of Smilax species extracts, which presented diverse mechanisms of action, such as quenching of superoxide anion, lipid peroxidation inhibition, deoxyribose degradation inhibition, and reducing power [29, 55].…”
Section: Discussionsupporting
confidence: 86%
“…However, CHCl 3 , SLG, and n -hexane extracts significantly reduced the lipid peroxidation. The phytochemical screening revealed the presence of low polarity compounds, such as coumarins and alkaloids, both inhibitors of lipid peroxidation [53, 54]. These results are in accordance with previous studies on antioxidant activity of Smilax species extracts, which presented diverse mechanisms of action, such as quenching of superoxide anion, lipid peroxidation inhibition, deoxyribose degradation inhibition, and reducing power [29, 55].…”
Section: Discussionsupporting
confidence: 86%
“…2C). The lack of effect under control conditions is surprising because flavonoids are well known for their antioxidant properties (Bubols et al, 2013) and they have been shown to be protective against a variety of excitotoxic insults by reducing oxidative stress (Cho and Lee, 2004, Silva et al, 2008, Campos-Esparza et al, 2009). However, the neuroprotective effects of rhamnetin during EWD suggest that the mechanism of enhanced excitotoxicity following ethanol exposure is a target for rhamnetin.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, coumarins are considered as a privileged scaffold in the design of compounds with several biological targets. Coumarin derivatives displayed a wide range of pharmacological activities like anti-cancer [188], among others [189][190][191][192][193].…”
Section: Coumarin Derivativesmentioning
confidence: 99%